Comparative Assessment of Heart Rate Variability Obtained via Ambulatory ECG and Polar Heart Rate Monitors in Healthy Cats: A Pilot Study - Grigg, Emma K.; Ueda, Yu; Walker, Ashley L.; Hart, Lynette A.; Simas, Samany; Stern, Joshua A. (Frontiers in Veterinary Science, 2021)
Chronic exposure to stressful environments can negatively impact cats’ health and welfare, affecting behavioral, autonomic, endocrine and immune function, as with cats in shelters. Low-stress handling practices likely improve shelter cat welfare, but data supporting improved outcomes remain limited. Cardiac activity, particularly heart rate variability (HRV), is an indicator of stress and emotional state in humans and non-human animals, tracking important body functions associated with stress responsiveness, environmental adaptability, mental and physical health. HRV studies in cats are limited, involving mainly anaesthetized or restrained cats. This pilot study tested the feasibility of obtaining HRV data from conscious cats, using a commercially available cardiac monitoring system (Polar H10 with chest strap), compared with data from a traditional ambulatory electrocardiogram. Simultaneous data for the two systems were obtained for five adult cats. Overall, the Polar H10 monitor assessments of HRV were lower than the true HRV assessment by ambulatory ECG, except for SDNN. Correlation between the two systems was weak. Possible reasons for the lack of agreement between the two methods are discussed. At this time, our results do not support the use of Polar H10 heart rate monitors for studies of HRV in cats.